Effects of genetic screening on perceptions of health: a pilot study. Issue 1 (January 1992) - Marteau, T M; van Duijn, M; Ellis, I
Abstract : The aim of the current study was to determine how carriers of a recessive gene, which confers no risk to their own health, perceive their health, relative to non-carriers. Perceptions of health in three groups were compared: those screened and found to carry the gene for Tay-Sachs disease, those screened and not found to carry the gene for Tay-Sachs disease, and a community based sample who, it was presumed, had not undergone screening. The groups did not differ in their perceptions of their current health or their past health. Carriers, however, viewed their future health with less optimism than the other two groups. The causes and consequences of this altered perception need to be explored in future studies. With the advent of population based screening for cystic fibrosis carrier status, these results highlight the importance of assessing in detail people's experiences of screening before the introduction of any mass genetic screening programmes.